Aldol–Tishchenko Reaction of α-Oxy Ketones: Diastereoselective Synthesis of 1,2,3-Triol Derivatives - Sedano, Carlos; Virumbrales, Cintia; Suárez-Pantiga, Samuel; Sanz, Roberto (Synthesis, 2021)
α-Oxy ketones, easily accessible by conventional routes, can be selectively deprotonated generating an enolate intermediate, which upon treatment with paraformaldehyde undergoes an aldol–Tishchenko reaction, leading to relevant 1,2,3-triol fragments in a totally diastereoselective manner. The excellent stereocontrol in the generation of a quaternary stereocenter is attributed to stereoelectronic effects in the Evans intermediate. This methodology allows overcoming some limitations of our previously reported strategy, based on the reaction of α-lithiobenzyl ethers with esters and paraformaldehyde, broadening the scope of the obtained polyols. Synthetic applications of this process include the preparation of a new dilignol model and some functionalized oxetanes.
Keywords: aldol–Tishchenko reaction; enolates; α-oxy ketones; polyol derivatives; diastereoselectivity; oxetanes